Experiences of the Pharmacy-Led Weight Management Service: Views of Service Providers in England - Peletidi, Aliki (Pharmacy (Basel), 2019)
Obesity constitutes one of the main modifiable risks of developing cardiovascular disease. In the UK, in 2016, 30% of the adult population were obese (30% of females and 29% of males). Community pharmacies are ideally situated to offer weight management (WM) services, enabling individuals to control and lose their excess weight. This study aimed at exploring the views of the pharmacy-led WM service providers in England. Semi-structured interviews were conducted with 15 trained community pharmacists and pharmacy staff—11 (73.3%) from Kent, three (20%) from Kingston and Richmond and one (6.7%) from Hackney and City—offering the WM service, either owning or working in independent pharmacies or for pharmacy chains. All interviews were audio-recorded, transcribed and anonymised. The analysis was conducted using thematic analysis. Three themes emerged: training and support, barriers and approach. Interestingly, service providers (SP) stated that obesity is a tough topic to talk about: they found it difficult to start a conversation about it, even if they had received training to facilitate this role. Additionally, several barriers for running such a service were identified, such as lack of time, too much work pressure and too little advertising, which could potentially lead to poor sustainability of the service. SPs can effectively intervene in an individual’s weight through the WM service that they offer. It is clear that further training should be provided in order for SPs to feel more comfortable in approaching and communicating with people and to increase the public’s awareness of the pharmacy-led WM service, so as to ensure the service’s sustainability.